Educational activities of Czech Museums (based on the example of fine arts Gallery in city Havlichkuv Brod) - Olha Velenkevych (Vasyl Stefanyk Precarpathian National University, 2017)
The article describes main aspects of museum pedagogic, its creation and development, the branches of modern researches in the field of museum pedagogic. The article is devoted to a definition of the place and the role of the pedagogy of museum in organization of the cultural and educational process in museum. The article reveals the history of development of the term "museum pedegogy as a scientific discipline". Educational functions of the museum pedagogy and their implementation in practice in the school museums were selected. Key words: museum pedagogic, children museum, pedagogic technologies, activities programs of museum and school, cultural and educational activity of museum, innovational methods, educational space of museum.